A bioinspired hybrid membrane with wettability and topology anisotropy for highly efficient fog collection. Issue 1 (11th December 2018) - Hu, Rongjun; Wang, Nü; Hou, Lanlan; Cui, Zhimin; Liu, Jingchong; Li, Dianming; Li, Qingzhong; Zhang, Hailong; Zhao, Yong
Abstract : A hybrid membrane with asymmetric microtopology and anisotropic wettability realizes highly efficient fog collection. Abstract : Inspired by the asymmetric microgeometry of cactus spines and the alternate hydrophobic/hydrophilic micropattern of a desert beetle's back, we designed a hybrid membrane with asymmetric microtopology and anisotropic wettability that achieved highly efficient fog collection.